Multicolored MIS-C, a single-centre cohort study - Petra Varga; András Balajthy; Erika Biró; Bernadett Bíró; Zsolt Reiger; Edit Szikszay; Gábor Mogyorósy; Rita Káposzta; Tamás Szabó (BMC Pediatrics, 2023)
Abstract Background The aim of this study was to investigate the clinical and laboratory parameters that can predict the severity of Multisystem Inflammatory Syndrome in Children (MIS-C) at admission. Methods We conducted a single-center, partly retrospective, partly prospective, observational cohort study between November 1, 2020 and December 31, 2021, which included patients aged from 1 month to 19 years, meeting the diagnostic criteria of MIS-C. We categorized the patients into three subgroups based on clinical and laboratory markers and assessed the predictive value of these factors in terms of ICU administration and cardiac abnormalities. Results 53 patients were classified in the following subgroups: Kawasaki-like disease (group 1) (47.2%, n = 25), shock with or without acute cardiac dysfunction (group 2) (32%, n = 17), fever and inflammation (group 3) (20.8%, n = 11). Subgroup analysis revealed that patients with shock and KD at initial presentation had significantly more severe manifestation of MIS-C requiring intensive care unit (ICU) treatment. Of the initial laboratory values, only CRP showed a significant difference between the 3 clinical groups, being lower in group 3. 52.6% of patients were admitted to the ICU. The median length of ICU stay was 3 days (range 3–20). ICU admission was more likely in patients with shortness of breath, renal failure (AKI) and patients with significantly increased concentrations of ferritin, D-dimer, INR and significantly milder increase concentration of fibrinogen. We found that fibrinogen and ferritin levels are independent risk factors for ICU admission. Cardiac abnormalities were found in 56.6% of total (30/53), with the following findings: decreased left ventricular function (32%), coronary abnormality (11.3%), pericardial effusion (17%), arrhythmia (32.1%) and mitral regurgitation (26.6%). Diarrhea and conjunctivitis at the initial presentation with significantly elevated CRP, Pro-BNP and blood pH concentrations were found to be a potential predisposing factor for decreased cardiac function while Pro-BNP and pH were independent risk factors for MIS-C. Regardless of the initial symptoms of MIS-C, the outcome was generally favorable. Conclusions Clinical characteristics and baseline laboratory values ​​may help identify patients at increased risk for severe disease outcome, such as need for intensive care, presence of shock and decreased cardiac function. Trial registration Participation consent was not reqired and ethical considerations were unnecessary, since we did not perform any extra interventions, only the necessary and usual therapeutic and diagnostic methods were used.